GIANT STEP - Yanuar Ichsan; Erfan Lubis; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2015)
Abstract The proses of making and producing the music artwork “Giant Step” aimed at expressing the musicians’ experience that had a special meaning on the use of the harmony of two tones with the use of interval (the space between two tones) that had a huge space from the first tone to the combination tone with the electric bass as the instrument. The huge interval was used to create harmony in this artwork. Some of them were sekt, sept, octave, none, decime and undecime, the interval between the tone was based on the range of the fingers and the needs of this artwork. In this artwork, the writer used the fusion style in which there was a combination between rock, funk and jazz style. The writer aimed at performing an artwork that had an energy and spirit from Rock and Funk style as well as it got the harmony from the Jazz style so that it could give its special uniqueness and characteristics. Key Words: Giant, Step